Development as social transformation: reflections on the global problematique (Colorado, 1985)
The perspective of 'development as social transformation' offers a point of departure for grasping how and why capitalist development and underdevelopment coexist as intrinsic elements and as a dialectical expression of the world-system in evolution. And this, in turn, provides the key to understanding why programmes and political proposals directed towards individual factors or spheres (such as industrialization, technologization of agriculture, export-orientation) are utterly irrelevant and inappropriate to the historical nature of the causes of the present crisis of the world-system. The permanent crisis of the Third World, and the current acute global crisis, are not mere peripheral or epi-phenomena, whose threat to run out of control is some kind of unfortunate accident: they are the expression of a crisis of the system as such, a crisis rooted in the dynamics of the system's own development.
Keywords: Economic